2013
DOI: 10.1038/pr.2013.134
|View full text |Cite
|
Sign up to set email alerts
|

TARC/CCL17 gene polymorphisms and expression associated with susceptibility and coronary artery aneurysm formation in Kawasaki disease

Abstract: Background: Kawasaki disease (KD) is a systemic vasculitis of unknown etiology. Thymus and activation-regulated chemokine/chemokine ligand 17 (TARC/CCL17) is one of the Th2 chemokines and has been suggested as a candidate gene for conferring susceptibility to Th2 associated with allergy diseases. This study examined the correlation between gene polymorphisms and plasma levels of TARC/CCL17 in patients with KD and the outcomes of KD. Methods: A total of 381 KD patients and 564 controls were subjected to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Th2 immune response included IL-4 [7], IL-5, eosinophil [8] and CCL17 [9] were also reported to play some role in the immuneopathogenesis and outcome of KD [10]. Eosinophilia associated with KD was first described by Dr. Kawasaki et al [1] and was also found in coronary artery autopsies [11].…”
Section: Introductionmentioning
confidence: 99%
“…Th2 immune response included IL-4 [7], IL-5, eosinophil [8] and CCL17 [9] were also reported to play some role in the immuneopathogenesis and outcome of KD [10]. Eosinophilia associated with KD was first described by Dr. Kawasaki et al [1] and was also found in coronary artery autopsies [11].…”
Section: Introductionmentioning
confidence: 99%
“…14, 15 Recently, Lee et al found that CCL17 gene polymorphisms and their expression were associated with susceptibility and the formation of coronary artery aneurysms in Kawasaki disease. 16 Several previous studies have reported that the CCL17 SNP rs223828 (previously known as −431C>T) is associated with increased CCL17 expression. For example Sekiya et al found that subjects carrying the −431T allele had significantly higher serum CCL17 concentrations than those without this allele, indicating that the −431T allele may have a major effect on CCL17 production.…”
Section: Effects Of Ccl17 Snp Rs223828 On Ccl17 Promoter Activitymentioning
confidence: 99%
“…Low frequency of T allele may promote Th1 reaction which was associated with the pathogenesis of multiple sclerosis [43]. On the other hand, although T allele was less frequent in patients with Kawasaki disease, TARC level was higher in them than in control subjects [42], but this may be because duration of fever in these patients were longer than in controls [42]. Therefore, we suggest that this SNP may be associated with chemotaxis of Th2 cells.…”
mentioning
confidence: 78%
“…TARC/ CCL17 induces the recruitment and migration of Th2 cells, affecting the susceptibility of Th2-associated disease such as atopic dermatitis and bronchial asthma [39,40]. The frequency of the T allele of the rs223828 SNP, which has higher transcription activity, was lower in patients of Kawasaki disease and multiple sclerosis than in controls [41][42][43]. Low frequency of T allele may promote Th1 reaction which was associated with the pathogenesis of multiple sclerosis [43].…”
mentioning
confidence: 99%